Ð’Ð¿Ð»Ð¸Ð² Ð¿Ñ€Ð¸Ñ€Ð¾Ð´Ð½Ð¾Ð³Ð¾ Ñ– Ñ€Ñ–Ð·Ð½Ð¸Ñ… Ð²Ð¸Ð´Ñ–Ð² ÑˆÑ‚ÑƒÑ‡Ð½Ð¾Ð³Ð¾ Ð³Ñ–Ð¿Ð¾Ð¼ÐµÑ‚Ð°Ð±Ð¾Ð»Ñ–Ð·Ð¼Ñƒ Ð½Ð° Ð°ÐºÑ‚Ð¸Ð²Ð½Ñ–ÑÑ‚ÑŒ ÑÐ¸ÑÑ‚ÐµÐ¼Ð¸ Ð¿Ñ€Ð¾Ñ‚ÐµÑ—Ð½Ð°Ð·Ð° â€“ Ñ–Ð½Ð³Ñ–Ð±Ñ–Ñ‚Ð¾Ñ€ Ð¿Ñ€Ð¾Ñ‚ÐµÑ—Ð½Ð°Ð· Ñƒ Ñ…Ð¾Ð¼â€™ÑÐºÑ–Ð² Ñ– Ñ‰ÑƒÑ€Ñ–Ð² - Lomako, V. V.; Samokhina, L. M.; Shylo, O. V. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2024)
There were studied the peculiarities of the effect of natural in hamsters and different types of artificial (hypoxic-hypercapnic and aminasin induced) hypometabolism (HM) in rats on activity of protease – protease inhibitor system. In blood serum and nuclear-free fractions of 10% homogenates of the tissues of brain cortex, lungs, heart, liver and kidneys there was measured protease total activity (PTA), non-trypsin-like proteases (NTLP) and their inhibitors (αlpha-1-protease inhibitor (αlpha-1-PI)) and α-2-macroglobulin (αlpha-2-MG) using highly sensitive (10–9–10–10 g) enzyme methods. Effects of various types of artificial and natural HM cause similar changes: the PTA increases on the background of unchanged activity of αlpha-1-PI. In contrast to natural HM during artificial one the activity of αlpha-2-MG increase (during natural HM it does not change). The most versatile differences in the dynamics of NTLP activity have been revealed: during natural HM it does not change (except kidneys), at hypoxic-hypercapnic HM it reduces and during aminasin induced one it vice versa rises (except liver, lungs and brain cortex). The findings are in the accordance with the concept that hypometabolism development, in particular natural one, is rather stipulated with the re-arrangements of certain molecular mechanisms, but not with the presence of specialized genes, i. e. re-programming of existing biochemical processes (for example, activity of protease – protease inhibitor system) takes place.